Algorithms for coverage mapping and optimizing beacon placement in a hybrid indoor positioning system - Sjöberg, Johannes; Johansson, Anton (My University, 2018)
This thesis considers a new analytical approach based on modeling indoor positioning as an coverage optimization problem. Over the recent years there has been extensive research in the subject of indoor positioning. Recent research commonly considers promising solutions by deploying new infrastructure, how ever, it does not often make use of already deployed infrastructure. The analytical approach proposed in this thesis considers the indoor environment and make use of meta heuristics to suggest how to extend existing infrastructure to create an reliable indoor positioning system. A prototype system has been implemented and several experiments have been performed at the expansion of existing Wi-Fi infrastructure with a Bluetooth low energy extension. The results showed that the system produces a reliable and affordable deployment design which uses very few reference nodes. How ever, this approach considers static environmental models and adaptors should be aware that this is best suited for indoor environments which are not subject to major refurbishments or renovations. Keywords:
Keywords: Data- och informationsvetenskap; Computer and Information Science